(untitled) (American Journal of Islam and Society, 2016)
This book is an important addition to the by-now rich collection of edited volumes and monographs published by Brill under the heading “Islamic History and Civilization: Studies and Texts.” It contains twenty-two essays written by leading scholars, historians, and philologists in honor of their late colleague and teacher Patricia Crone (professor of Islamic history, Institute for Advanced Study), who passed away a few months after the publication of the volume. For students of Islam, Crone needs no introduction. Her scholarship has marked the field through its erudition as well as its distinctive boldness and controversial nature that, at times, drew virulent criticism. Perceived by some as arrogant and hasty, by others as incisive and daring, she was not one to mince words. This volume, starting with an intimate “memoir” by Judith Herrin and concluding with an appreciative scholarly review by Chase Robinson, tends to overlook Crone’s divisive personality and does much to present her as an ideal academic and mentor. She was, as the editors lyrically phrase it, a “seeker and lover of truth.” ...